An ultrasensitive impedimetric glycan biosensor with controlled glycan density for detection of lectins and influenza hemagglutinins† - Hushegyi, A. (Chem Commun (Camb), 2015)
An impedimetric glycan biosensor with optimised glycan density was applied for the detection of lectins and influenza hemagglutinins down to attomolar concentrations (aM).